PREVENTION OF TEACHERS’ EMOTIONAL EXHAUSTION - Mir Jalalli, Narmin (Health and Society, 2024)
The article explores the issue of professional exhaustion among educators. It discusses changes in perceptions of professional exhaustion over time and identifies primary theoretical approaches to understanding the concept and its psychological and physiological aspects. The article also categorizes the factors contributing to educators’ professional exhaustion and classifies stressors of a professional nature. It establishes the phases of professional exhaustion experienced by educators and outlines its primary symptoms. Additionally, it assesses the impact of psycho-physiological exhaustion on the effectiveness of pedagogical activities and the education system. The article analyzes the relevance of applying prevention measures for professional exhaustion and outlines individual and group-based prevention techniques. It recommends developing and cultivating individual characteristics to decrease the likelihood of professional exhaustion. It details methods for acquiring stress management skills, including regulating personal, social, and physical well-being, modifying thought processes, and logical thinking. Lastly, the article presents universal approaches to combating professional stress factors.